2020
DOI: 10.1038/s41598-020-61493-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep quality and time with energy metabolism in sedentary adults

Abstract: the aim of the present study was to investigate the relationship of sleep quality and time with basal metabolic rate (BMR) and fuel oxidation in basal conditions and during exercise in sedentary middleaged adults. We also studied the mediation role of dietary intake and adherence to the traditional Mediterranean Diet in the relationship between sleep parameters and energy metabolism parameters.A secondary analysis of the FIT-AGEING study was undertaken. 70 middle-aged sedentary adults (40-65 years old) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
(66 reference statements)
0
13
2
Order By: Relevance
“…Fibre intake did not have a mediating role between the association of PSQI with fat oxidation. Alterations of sleep pattern over time and variations of individuals' body composition and metabolic status might explain the inconsistent results 105 . The relationship between PDI and hPDI with sleep quality did not reach significant levels in the current study.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Fibre intake did not have a mediating role between the association of PSQI with fat oxidation. Alterations of sleep pattern over time and variations of individuals' body composition and metabolic status might explain the inconsistent results 105 . The relationship between PDI and hPDI with sleep quality did not reach significant levels in the current study.…”
Section: Discussioncontrasting
confidence: 88%
“…94,99 Previous observational studies have shown that short sleepers have poorer dietary quality with lower intakes of fruits, vegetables, whole grains, and beans. 100 105 The relationship between PDI and hPDI with sleep quality did not reach significant levels in the current study. This might be explained by the fact that socioeconomic status is a determining factor in sleep health.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In order to ensure that the participants were “good sleepers” and in addition to the scores of PSQI, a sleep monitor (SenseWear™, Body Media ® , Pittsburgh, PA, USA) was provided to be worn on their non-dominant arm for 23 h a day for one whole week prior to the experimental conditions, as well as 2 days leading up to the RSE and SSE conditions. Data from the sleep monitor were used to characterize sleep and physical activity levels [ 63 , 64 , 65 , 66 , 67 , 69 , 70 ], as the participants had to be “good responders” and to refrain from physical activities for 2 days prior to the RSE and SSE conditions. In addition to sleep and physical activity requirements, the participants had to control and monitor their diets for the same period (i.e., 1 week prior and 2 days leading to the experimental conditions).…”
Section: Methodsmentioning
confidence: 99%